Practical experience with the OECD transfer pricing guidelines : proceedings of a seminar held in London, in 1998 during the 52nd Congress of the International Fiscal Association /: proceedings of a seminar held in London, in 1998 during the 52nd Congress of the International Fiscal Association. (2016) - Unknown
No abstract available